Technology and Older Women: Considerations Regarding Their Use and Misuse - Chyrisse Heine; Susan Feldman (Frontiers Media S.A., 2022)
Health and wellbeing are inextricably linked to an individual's capacity for continued meaningful engagement and connection with the world around them. Technological innovations designed to maximize the quality of life for older women range from sophisticated bio-medical interventions to ordinary day-to-day communication devices. Many innovations can ensure a higher quality of life for older women and support and care as required.In this article, we consider: (1) The range of appropriate technologies currently available for older women, their families and communities. (2) The way technology contributes to the maintenance of optimum physical health and wellbeing for older women. (3) The significant challenges and considerations associated with the incorporation of technologies into their daily lives.